2018
DOI: 10.1016/j.arth.2017.08.036
|View full text |Cite
|
Sign up to set email alerts
|

Trabecular Metal Acetabular Components Reduce the Risk of Revision Following Primary Total Hip Arthroplasty: A Propensity Score Matched Study From the National Joint Registry for England and Wales

Abstract: Background Trabecular metal (TM) coated acetabular components are increasingly used in both primary and revision total hip arthroplasty (THA). However, previous studies assessing TM acetabular components have been small single-centre cohorts with most lacking a control group. We compared revision rates following primary THA between TM and non-TM coated acetabular components. Methods A retrospective observational study was performed using National Joint Registry data, which included primary THAs with the same c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
28
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 23 publications
3
28
1
1
Order By: Relevance
“…Three registry studies have subsequently assessed the effect of TM on future infection [8,9,11]. In the NJR for England and Wales we earlier reported lower revision rates for infection when TM (versus non-TM) was used in primary THA [9], but no difference in re-revision rates for infection when TM was used for all-cause revision THAs [11]. The latter findings in allcause revisions were also confirmed in a study from the Swedish and Australian registries [8].…”
Section: Discussionmentioning
confidence: 78%
See 4 more Smart Citations
“…Three registry studies have subsequently assessed the effect of TM on future infection [8,9,11]. In the NJR for England and Wales we earlier reported lower revision rates for infection when TM (versus non-TM) was used in primary THA [9], but no difference in re-revision rates for infection when TM was used for all-cause revision THAs [11]. The latter findings in allcause revisions were also confirmed in a study from the Swedish and Australian registries [8].…”
Section: Discussionmentioning
confidence: 78%
“…It was suggested that TM was protective against infection after revision, and that TM may be useful when revising THAs for PJI. Three registry studies have subsequently assessed the effect of TM on future infection [8,9,11]. In the NJR for England and Wales we earlier reported lower revision rates for infection when TM (versus non-TM) was used in primary THA [9], but no difference in re-revision rates for infection when TM was used for all-cause revision THAs [11].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations